Comparação entre o teste de tolerância à insulina e o teste da clonidina para o diagnóstico de deficiência do hormônio de crescimento idiopática em crianças com baixa estatura - FARINASSI, Ana Luiza Prieto (2019)
Longitudinal growth involves genetic, hormonal, nutritional and environmental aspects. Despite other causes of short stature (SS), Growth Hormone Deficiency (GHD) must be investigated. The investigation is carried out by the analysis of auxological data, being necessary the physiological stimulation of growth hormone secretion, through provocative tests, as a complementary method. Although, it is necessary a better comprehension of these tests, as well the determination of most appropriate peak cut-off value for correct diagnosis of GHD. The purpose of this project is to compare insulin tolerance test (ITT) and clonidin test (CT), establishing sensibility (SEN), specificity (SPE) and accuracy (ACC) in different cutoffs for GHD’s diagnosis. A study was carried out with 57 children and teenagers, who had <2SD height for age and sex and/or <-1SD for parental height. The diagnosis of GHD was confirmed in those patients with SS and, at least, 0,3SD height increase in a year, or proportional, in a minimum period of six months follow-up with rhGH treatment. SEN, SPE and ACC of ITT and clonidin test were defined for 3, 5, 7 and 10g/L values. Among the patients in the study 25 (43,9%) and 32 (56,1%) were classified as SS with and without GHD, respectively. The cut-off founded for ITT was <7 µg/L (S: 90%, E: 77%, A: 83%) and for CT was <5µg/L (S: 86%, E: 85%, A: 86%). This study concludes that <7µg/L represents the most appropriate cut-off value for ITT in diagnosis of GHD. When clonidin test was applied, < 5µg/L cut-off is more suitable. Clonidine test presented greater sensibility than ITT at all cutoff values.